Akame ga kill! Zero 3 - Takahiro, 1981- (Yen Press, 2016)
"Kurome and her team set out in search of the king's grave but end up captured by the grave keepers! Akame's team heads out to rescue her--will the two sisters finally be reunited?!"--Page 4 of cover.